Psychological drivers of electric vehicle battery recycling: the impact of place attachment and sustainable attitudes - Cheng, Jie; Gao, Tian; Zhang, Yi-Cheng; Khan, Noor Ullah; Lu, Ke-Bin (Frontiers in Psychology, 2026)
IntroductionThe rapid expansion of electric‑vehicle adoption in China has intensified concerns about end‑of‑life management of power batteries. Despite increasing apprehensions about economic, social, and environmental sustainability 2021-2035, there has been a noticeable surge in scholarly interest directed towards formal power battery recycling. Although psychological drivers are key to participation through the lens of behavioral reasoning theory, the role of place attachment remains underexplored, particularly in collectivist cultures. Bridging this research lacuna, the current study offers an in-depth and holistic investigation of how the multidimensional facets of place attachment influence residents’ economic, social, and environmental attitudes and how attitudes affect their intention towards formal recycling.MethodsA questionnaire survey was administered to 427 permanent residents of Hefei, a pilot city for electric vehicle and battery recycling initiatives. Data were analyzed using Partial Least Squares Structural Equation Modeling to test the hypothesized pathways linking place attachment dimensions to sustainable attitudes and recycling intentions.ResultsThe findings reveal that nature bonding is the strongest predictor across all three attitudes, economic attitude exerts the most powerful direct effect on recycling intention, and the combined sustainable attitudes explain 44.9 % of the formal recycling intention.DiscussionThese results demonstrate that stronger emotional and cognitive ties to one’s locality significantly enhance pro‑recycling attitudes, whereas attitudes affect the willingness to participate in formal power battery recycling channels. Effective power battery recycling campaigns in collectivist contexts should therefore move beyond generic appeals and leverage residents’ specific attachments to their community’s nature, economy, and social fabric. This study contributes to environmental psychology by integrating place‑attachment constructs into a reasoning‑based model of sustainable behavior, and offers actionable insights for municipal authorities, recycling firms, and community groups seeking to improve formal recycling rates and advance circular‑economy objectives in rapidly urbanizing regions.